Self-Discharge Resistance Values at Different Initial Charge and Temperature Levels - Yousif, S E; Auger, Daniel; Fotouhi, Abbas; Propp, Karsten (Cranfield University, 2017)
Table II: Self-discharge resistance values at different initial charge and temperature levels from 'Self-Discharge Effects in Lithium-Sulfur Equivalent Circuit Networks for State Estimation'. Opens with Microsoft Excel.
Keywords: lithium-sulfur battery'; 'self-discharge'; 'equivalent circuit network'; 'state estimation'; 'Engineering not elsewhere classified'